Patient satisfaction and self-reported dry eye symptoms in hyperopic patients treated with femtosecond laser in situ keratomileusis - Mäkinen, Petri (Clin Ophthalmol, 2019)
PURPOSE: To study self-reported patient satisfaction and dry eye symptoms in hyperopic correction with femtosecond laser-assisted in situ keratomileusis (FS-LASIK). PATIENTS AND METHODS: Ninety-eight eyes (53 patients) were treated with FS-LASIK for hyperopia. Patients’ self-reported dry eye symptoms and satisfaction with near and far vision were graded on the visual analog scale (VAS) preoperatively and 1 month postoperatively. RESULTS: Ninety-one percent of the eyes with the plano target (54 eyes) achieved an uncorrected distance visual acuity of 20/20 or better. Predictability, defined as spherical equivalent refraction within ±0.5 D of target, was 88% of all eyes. None of the eyes lost two or more Snellen lines of corrected distance visual acuity. There was no significant change in the self-reported dry eye sensation (VAS score from 2.7±2.0 to 2.8±2.0; P=0.66). In 44 monovision patients, satisfaction with both far vision (from 71.2±19.8 to 89.2±8.7; P<0.0001) and near vision (from 51.7±26.2 to 89.3±13.2; P<0.0001) increased significantly. In nine emmetropic patients, satisfaction with neither far vision nor near vision was significantly improved, although there was a clear tendency (from 73.7±23.7 to 86.9±15.3; P=0.22, and from 58.9±29.1 to 81.6±17.4; P=0.11, respectively). In the monovision patient group, far vision satisfaction decreased when dry eye symptoms increased. Monovision patients, as predicted, were more satisfied with their near vision, when postoperative spherical equivalent from target was on the myopic side. CONCLUSION: FS-LASIK correction of hyperopia significantly improved patient satisfaction with both near and far vision in monovision patients. Hyperopic patients had no significant changes in postoperative dry eye symptoms compared to preoperative values.